Basal and Insulin Mediated VLDL-Triglyceride Kinetics in Type 2 Diabetic Men - Sørensen, Lars P. (American Diabetes Association, 2011)
OBJECTIVE: Increased very-low-density lipoprotein triglycerides (VLDL-TG) concentration is a central feature of diabetic dyslipidemia. The objective was to compare basal and insulin mediated VLDL-TG kinetics, oxidation, and adipose tissue storage in type 2 diabetic and healthy (nondiabetic) men. RESEARCH DESIGN AND METHODS: Eleven type 2 diabetic and 11 healthy men, matched for BMI and age, were included. Ex vivo-labeled VLDL-TG tracers, blood and breath samples, fat biopsies, indirect calorimetry, and body composition measures were applied to determine VLDL-TG kinetics, VLDL-TG fatty acids (FA) oxidation, and storage in regional adipose tissue before and during a hyperinsulinemic euglycaemic clamp. RESULTS: VLDL-TG secretion was significantly greater in diabetic compared with healthy men (basal: 86.9 [31.0] vs. 61.9 [30.0] μmol/min, P = 0.03; clamp: 60.0 [26.2] vs. 34.2 [17.9] μmol · min(−1), P = 0.01). The insulin mediated suppression of VLDL-TG secretion was significant in both groups. VLDL-TG clearance was lower in diabetic men (basal: 84.6 [32.7] vs. 115.4 [44.3] ml · min(−1), P = 0.08; clamp: 76.3 [30.6] vs. 119.0 [50.2] ml · min(−1), P = 0.03). During hyperinsulinemia fractional VLDL-TG FA oxidation was comparable, but in percentage of energy expenditure (EE), significantly higher in diabetic men. Basal VLDL-TG storage was similar, but significantly greater in abdominal compared with leg fat. CONCLUSIONS: Increased VLDL-TG in type 2 diabetic men is caused by greater VLDL-TG secretion and less so by lower VLDL-TG clearance. The ability of hyperinsulinemia to suppress VLDL-TG secretion appears preserved. During hyperinsulinemia VLDL-TG FA oxidation is significantly increased in proportion of EE in type 2 diabetic men. Greater basal abdominal VLDL-TG storage may help explain the accumulation of upper-body fat in insulin-resistant individuals.